1992
DOI: 10.1073/pnas.89.22.10930
|View full text |Cite
|
Sign up to set email alerts
|

Induction of aP2 gene expression by nonmetabolized long-chain fatty acids.

Abstract: Long-chain fatty acids (FA) have been shown to regulate expression of the gene for the adipocyte FA-binding protein aP2. We examined whether this effect was exerted by FA themselves or by a FA metabolite. The a-bromo derivative of palmitate, an inhibitor of FA oxidation, was synthesized in the radioactive form, and its metabolism was investigated and correlated with its ability to induce aP2 in Ob1771 preadipocytes. a-Bromopalmitate was not utilized by preadipocytes. It was not cleared from the medium over a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 33 publications
2
75
0
4
Order By: Relevance
“…5). We could also localize these consensus sequences in the promoter region of the murine PAI-1 gene, as well as in the regulatory regions of the rat S14 and murine aP2 genes, both of which have been reported to be transcriptionally regulated by fatty acids [23,25] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). We could also localize these consensus sequences in the promoter region of the murine PAI-1 gene, as well as in the regulatory regions of the rat S14 and murine aP2 genes, both of which have been reported to be transcriptionally regulated by fatty acids [23,25] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation could be that the fatty acids are directly involved in transcriptional regulation of the PAI-1 gene. An interesting feature of the polyunsaturated fatty acids is their ability to regulate the expression of genes by binding to fatty acid responsive factors [22,23,25]. Sloots et al identified consensus nucleotide sequences in the upstream region of five oleic acid-inducible genes of the diploid yeast Candida lropicalis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, dietary fatty acids have been shown to regulate the gene expression of pancreatic GLUT2 and glucokinase (16), and long-chain fatty acids can induce the expression of the genes for the adipocyte fatty acid-binding protein aP2 (17) and liver carnitine palmitoyltransferase I (CPT I) (18). Additionally, the expression of a number of hepatic lipogenic, glycolytic, and gluconeogenic genes is regulated by polyunsaturated fatty acids at the transcriptional level (19,20).…”
mentioning
confidence: 99%
“…Ainsi, les bases moléculaires par lesquelles les AGPI affectent l'expression génique hépatique impliquent vraisemblablement au moins deux voies distinctes mettant en jeu soit des facteurs trans soit des éléments régulateurs en cis. Tandis que la répression de l'expression génique semble être due aux AGPI, les acides gras saturés et insaturés sont capables de stimuler l'expression de gènes dans le foie [63] et dans le tissu adipeux blanc [64,65]. Le fait que les effets des AGPI sur l'expression génique soient rapides dans le foie et beaucoup plus lents dans le tissu adipeux est en faveur d'une régulation spécifique du type tissulaire considéré [58,48].…”
Section: Effet Des Acides Gras Polyinsaturés Sur L'expression Géniqueunclassified